Struktur Umur dan Sex Rasio Sub-Sub Populasi Simpai (Presbytis melalophos melalophos) pada Lanskap Campuran dalam Kawasan Hutan Lindung Bukit Daun - serly rahmadinie; Rizwar Rizwar; Darmi Darmi; Jarulis Jarulis; Sipriyadi Sipriyadi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The research aims to determine the number of individuals, age structure and sex ratio in the Simpai population or sub-population in the Bukit Daun Protected Forest. The research used the direct sencus method or direct counting of individual hoops (P. m. melalophos) in a sub-population in the field. Observations were carried out at 06.00-18.00 WIB and increased observations were carried out four times on different days. The research results show that there are three sub-populations of Simpai in the Bukit Daun Protected Forest Area. The number of individuals in the first sub-population is 10 individuals, the second sub-population is 13 individuals, and the third sub-population is 15 individuals. Based on the age structure, the number of young individuals, namely teenagers and children, including babies, in the third sub-population is greater (24 individuals) compared to adults (14 individuals). The sex ratio of adult male and female hoops, namely (1:3) in subpopulations I and II, is higher than subpopulation III (1:2), whereas in the juvenile group, the sex ratio in subpopulation III (1:4) is higher than subpopulation I and II (1:2). Keywords: Bukit Daun Protected Forest, Sex ratio, Hoop, Age Structure, Subpopulation